Física computacional: una propuesta educativa - Rojas, J.F.; Morales, M.A.; Rangel, A.; Torres, I. (Revista Mexicana de Física E, 2009)
Nowadays there exist programming languages whose characteristics make them a very good didactic tool for learning many topics of physics. There are, also, typical learning physical problems that can not be completely explained and even understood using the blackboard, because they present a kind of complex behaviors such as non linearties or many degrees of freedom. That is why they do not have any analytical solution. In any case Computational Physics method is an alternative teaching tool what in practice contains all of the topics of basic programming and numerical methods. In this paper we aboard some issues, enable us, to conform what we will call ``algorithmic education’’. We present some traditional physics education problems, based on numerical and visual algorithms, for a better conceptual understanding and models build up by the students it self. Just by using some elementary programming modules, we propose a strategy to build up models starting from a pre-differential conceptual interpretation, which can be particularly useful in the first period of university. The contribution consists in by using a few mathematical elements and resources, students can make more and more complex simulation models. Specifically, for the implementation of the ``algorithmic education´´ we have used python, a programming language what permits the develop of themes covering from the free particle movement, and damped harmonic oscillators, as well as the ideal or hard spheres gases and even Brownian motion walks. In all of these cases the same elementary programming modules have been used.